2002
DOI: 10.1016/s0964-8305(01)00118-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flight ControlR to reduce blackbird damage to newly planted rice in Louisiana

Abstract: Blackbirds cause extensive damage to newly planted and ripening rice. To date there is not a registered bird repellent for reducing this damage. We evaluated Flight ControlK, a 50' ' anthraquinone product, as a potential repellent to blackbirds in cagc and field tests in Louisiana. In one-and no-choice cage tests, brown-headed cowbird and red-winged blackbird consumption of 2%) Flight controlR treated ricc seed was significantly reduced. In a subsequent field tcst. 2% Flight controlR was effective in reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Nonlethal chemical repellents are a socially acceptable approach to managing avian depredation of agricultural crops (Cummings et al, 2002a(Cummings et al, , 2002bLinz et al, 2006;Werner et al, 2011). Previous studies assessing chemical repellents, for ripening field and sweet corn, have shown mixed results in reducing damage by birds (Woronecki et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlethal chemical repellents are a socially acceptable approach to managing avian depredation of agricultural crops (Cummings et al, 2002a(Cummings et al, , 2002bLinz et al, 2006;Werner et al, 2011). Previous studies assessing chemical repellents, for ripening field and sweet corn, have shown mixed results in reducing damage by birds (Woronecki et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Depredating blackbirds (Icterids) can negatively impact growth of newly planted rice in the mid-South of the United States and production of ripening rice and sunflower (Cummings et al 2002;Avery et al 2005;Werner et al 2005Werner et al , 2007Werner et al , 2008a. Cummings et al (2005) estimated that blackbirds caused approximately US$13.4 million of damage to United States rice production in 2001.…”
mentioning
confidence: 99%
“…Red‐winged blackbirds have consistently demonstrated repellency to AQ‐treated rice seed. Repellency has been positively associated with AQ concentrations as low as 50 mg AQ kg −1 and up to 20 000 mg AQ kg −1 , regardless of the tested product . A threshold concentration of 4921 mg AQ kg −1 on rough rice was predicted for 80% repellency in red‐winged blackbirds; this concentration also causes conditioned avoidance in investigations of sensory cues .…”
Section: Avian Seed Treatmentsmentioning
confidence: 96%
“…Field testing of AQ‐treated rice seed in water‐seeded field tests in Louisiana demonstrated that rice seed treated with 7100–8800 mg AQ kg −1 at planting was effective for blackbird repellency . Anthraquinone‐treated plots had higher plant density than control plots at the conclusion of the study, and bird activity within control plots was twice that observed within treated plots .…”
Section: Avian Seed Treatmentsmentioning
confidence: 98%